Analisis LQshift LQshare Untuk Mengukur Dampak Perluasan Kota Terhadap Kinerja Ekonomi Regional (Studi Kasus: Perluasan Kota Manado Terhadap Perekonomian Wilayah Sulawesi Utara) - Harun, Uton Rustan; Canon, Syarwani (The ITB Journal Publisher, 2006)
Manado is a nodal ofÂ Â Northern Sulawesi Region where ManadoÂ itselfÂ hasÂ predominantÂ functionÂ Â ascenterÂ forÂ administrative,socio-economicÂ developmentÂ andpublicÂ services.Â ThoseÂ functions seem to be overloaded if the area of the city is still limited, so in 1988 the area of municipal Manado has extended to surrounding area into approximately 6.64 time (Government Decree 22, 1988). The extension of the urban area has some doubtful to discussed both for academician and practitioner. LQ analysis has been known well for practitioner as general investigation methods of the comparative advantage among the regional economic sectors or activities. The Evaluation Method for regional economic sector comparation (LQShare LQShift Analyis) has developed base on the regional economic analysis called Shift-share Analysis compounding vocational quotient and its derivate. This Evaluation Method aimed to identified the role and shifted the regional economic sectors within period of time, and we can detected which are the most competitiveness among the sectors. The modesl have the similarity with the original model of LQ analysis, so practically those model interdependency to identify the competitiveness of the roleâs sector. Based on these models we can predicts the shifting sectors and itâs comparative competitiveness in the future and also able to predicts the impact of certain extention area into larger region such as extention of urban area into regional economic performance aswhole.Keywords: Sectoral specialization/concentration, sectoral development, income distribution.